Model Based Design Development and Testing - K, Harshita; S, Ankitha B; Shivputra, Shivputra (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
Hardware-in-the-loop (HIL) simulation is a technique that is used in the development and test of complex process systems. HIL simulation provides an effective platform by adding the complexity of the plant under control to the test platform. The complexity of the plant under control is included in test and development by adding a mathematical representation of all related dynamic systems. These mathematical representations are referred to as the plant simulation.